Monitoring and Control Design of Automatic Transfer Switch-Automatic Main Failure with Human Machine Interface (HMI) - Khafidzati 'Ulya; Yahya Chusna Arif; Lucky Pradigta Setiya Raharja (Universitas Ahmad Dahlan, 2022)
Automatic transfer switch-Automatic main failure is a commonly used technology for shifting supply from PLN to a generator in the case of a PLN blackout. The ATS-AMF module system frequently employs a PLC, which comes at a high cost, and the system alarm information only is seen by the user close to the system. The purpose of this research is to design an automatic transfer switch-automatic main failure system that used SCADA to improve the reliability of electricity supply by providing notification alarm information and buzzers. This research contribution is a development of an automatic transfer switch-automatic main failure, which can be used as a simulator for studies on measuring voltage, current, power, and frequency of main power supply in real cases. Furthermore, this instrument is used fuel level and temperature measures for its backup power (Genset), the result of measures will be monitored SCADA system with the available failure data, alarm logs, and status logs recorded in historical data, which is designed at a low cost and is easy to use. This information result of the measured sensor will be transferred in real-time to the SCADA system, so can be directly obtained for analysis. The main components for this system are microcontroller STM32 Nucleo, PZEM 004T sensor, ultrasonic sensor, DS18B20 sensor, ethernet, and VTSCADA. The result of this system is the temperature detects 89oC, and alarm information has been sounded with the statement “Genset Temperature Warning HIGH” thus instructing the generator to turn off the system. Meanwhile, based on the results of the fuel adjustment test, SCADA gives the information “Genset Fuel Level Warning LOW” when setting the fuel at 36%. The data historical viewer that stores up to 6 months and alarm information for the warning system on the SCADA has been successfully designed.